„Słowa zaklęte w poezji”. O autoterapeutycznych właściwościach poezji na przykładzie twórczości Katarzyny Dominik - Matras-Mastalerz, Wanda; Kania, Marcin (eBooki.com.pl, 2014)
The article presents self-therapeutic poetry written by Katarzyna Dominik -the author suffering from bone marrow myelodysplasia. Her poems, published in three books, are an interesting example of a connection between the author’s individual experience and her poetry. The poems written by Katarzyna Dominik show her reflections on the disease and the relations with other people; they exhibit her deep need to bear testimony to the experienced suffering and the ways to overcome it. The analysis of the author’s poetic works is preceded by a presentation of the selected issues connected with therapy through poetry as one of the methods of therapy and self-therapy.
Keywords: catharsis in poetry; methods of therapy; selftherapy; therapeutic power of poetry; Katarzyna Dominik